Prioritized Mapping in Bali: Multi-View Hierarchical Agglomerative Clustering (MVHAC) Approach - Andika, Gede; Arsyad, Lincolin (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 1, Februari 2023 (pp.1-186), 2023)
This study aims to determine which sectors and areas should be prioritized in development in BalI. The data used is panel data from 2010 – 2022 for all districts/cities in Bali. The data analysis technique for mapping sectors and regions is Multi-View Hierarchical Agglomerative Clustering (MVHAC). The results of the analysis of Location Quotient and Dyanmic Location Quotient show that the SARBAGITA area (Denpasar, Badung, Gianyar, and Tabanan) has potential in the secondary and tertiary sectors, while other areas are in the primary sector. MVHAC analysis shows that in quadrant 1 (cluster 1), namely Badung and Denpasar, the sectors that can be developed are agriculture, forestry and fisheries; real estate; manufacturing industry; water supply, waste management and waste recycling and mining and excavation, the area of quadrant 3 (cluster 2) of Tabanan and Gianyar is almost similar to Badung and Tabanan, but the potential sector is also transportation and warehousing, while quadrant 4 (cluster 2) is more on the information and communication; real estate; educational services; health services and social activities.